Comparison of meniscal T1rho- and T2*-relaxation times in professional female volleyball players and healthy controls using 3T MRI: A pilot study. Issue 155 (October 2022) - Spink, C.; Henes, F.O.; Da Cruz, L.; Sinn, M.; Behzadi, C.; Schoen, G.; Welsch, G.H.; Adam, G.; Bannas, P.; Maas, K.J.
Abstract: Purpose: Comparison of meniscal T1rho- and T2*-relaxation times in professional female volleyball players and healthy controls to determine if relaxation times are prolonged in athletes due to compositional meniscal alterations based on extensive and repetitive joint loading. Methods: The right knee of 20 asymptomatic professional female volleyball players and 20 female controls were examined at 3T MRI. T1rho- and T2*-measurements were performed in sagittal orientation. For quantitative measurements, two readers independently defined two consecutive central slices with the greatest area of the anterior and posterior horn of the lateral (AHLAT; PHLAT) and medial meniscus (AHMED; PHMED). Both readers repeated measurements after a six-week interval on the original MR images. Statistical analysis included intraclass correlation coefficient (ICC), Wilcoxon signed-rank-, Shapiro-Wilk- & Kolmogorov-Smirnov- and Mann-Whitney U-tests. Results: Mean T1rho-relaxation times in the PHMED were significantly prolonged in professional female volleyball players when compared to controls (24.2 ± 4.0 vs 21.1 ± 2.6 ms; p < 0.005). There were no significant differences for the remaining three meniscal horns. T2*-relaxation times revealed no significant differences between athletes and controls. Prolonged T1rho-relaxation times in the PHMED of female volleyball players did not correlate with significant change in T2*-relaxation times within all meniscal subregions. Reproducibility levels were excellent in all segments (Interobserver-ICC: 0.93–0.97 and intraobserver-ICC: 0.97–0.99). Conclusion: T1rho-relaxation times were significantly increased in the PHMED of female volleyball players, potentially indicating a predilection to early degenerative meniscal changes. T1rho may serve as a sensitive biomarker at detecting early compositional meniscal alterations in athletes.